Diversity and Sustainability: The Role of Traditional Fruit Trees in Uttarakhand Agricultural Landscape - Saraswati Nandan Ojha; Aradhana; Maneesha Singh (International Journal of Land, 2024)
Uttarakhand state is characterized by a rich diversity of traditional fruit trees. Uttarakhand is largely a mountainous state, with only around 10% of its overall geographical area being plains, and more than three-quarters (78%) of its total people relying on agriculture for survival. The state's geographical features and climatic circumstances are suited for growing temperate and subtropical fruit crops. It provides a variety of agro-geoclimatic conditions that are ideal for fruit cultivation. In this context, the current study on traditional fruits of Uttarakhand was conducted with the goal of identifying and exploring the ethnobotanical knowledge of these fruits. Some fruit plants data have been collected and got the information about their Botanical name, Local name, and ethno botanical uses. Traditional fruits, as a significant forest product, enhance the human diet by providing critical vitamins, minerals, and fiber required for good health. As a result, these fruits could be better utilized in terms of value-added products, as well as for human health promotion. Traditional edible fruits were cultivated by the local people for own consumption or direct edible purpose, and livelihood improvements.
Keywords: CVD; Nutritional; Prunus; Traditional; value